2020
DOI: 10.1038/s41567-020-0950-5
|View full text |Cite
|
Sign up to set email alerts
|

Hidden magnetism at the pseudogap critical point of a cuprate superconductor

Abstract: The mysterious pseudogap phase of cuprate superconductors ends at a critical hole doping level p* but the nature of the ground state below p* is still debated. Here, we show that the genuine nature of the magnetic ground state in La 2x Sr x CuO 4 is hidden by competing effects from superconductivity: applying intense magnetic fields to quench superconductivity, we uncover the presence of glassy antiferromagnetic order up to the pseudogap boundary p* ≈ 0.19, and not above. There is thus a quantum phase transiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 53 publications
7
66
1
1
Order By: Relevance
“…While we observe the same behaviour in LSCO p = 0.12 for B ≤ 2T (see Appendix B for more details), this scenario does not hold at higher field where we observe an increase of T min . All measurements reported here in LSCO p = 0.12 support the interpretation that the ultrasound anomalies are caused by the AFM glass phase via spin-phonon coupling [18].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…While we observe the same behaviour in LSCO p = 0.12 for B ≤ 2T (see Appendix B for more details), this scenario does not hold at higher field where we observe an increase of T min . All measurements reported here in LSCO p = 0.12 support the interpretation that the ultrasound anomalies are caused by the AFM glass phase via spin-phonon coupling [18].…”
Section: Discussionsupporting
confidence: 82%
“…Different interpretations have been proposed to explain this peculiar behaviour [11][12][13][15][16][17]. Recently, using NMR and sound velocity measurements in high magnetic field in LSCO for p ≥ 0.145, we have shown that the anomalous sound velocity appears to be caused by a coupling of the AFM glass to the lattice [18].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…, 引起了国际上的广泛关注. 铁基超 图29 (网络版彩图)不同掺杂和磁场下 139 La原子核的1/T 1 T随温度的变化 [85] . 导体发展至今, 已在多种不同的铁基材料中陆续发现 了高温超导现象 [88][89][90][91][92] .…”
Section: 消失了 这样的相图再次说明了Punclassified
“…Our interest in studying gauge theories of critical points in metals was motivated by numerous experimental indications [1][2][3][4][5][6][7][8][9][10][11][12][13][14] of optimal doping criticality in the hole-doped cuprate superconductors. We examine here further aspects of a recently proposed [15,16] SU (2) gauge theory for the vicinity of optimal doping in which a parent conformal theory is coupled to a large Fermi surface of gauge-neutral electrons.…”
Section: Introductionmentioning
confidence: 99%